2006
DOI: 10.3354/meps312169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved domoic acid on the grazing rate of krill Euphasia pacifica

Abstract: Some amino acids released from phytoplankton into the water are known to be feeding stimulants to zooplankton. However, domoic acid (DA), a neuroexcitatory amino acid released by some species of the diatom genus Pseudo-nitzschia, has the potential to be a feeding deterrent due to its neurotoxicity. Euphausiids (krill) are important members of the zooplankton grazer community and key prey items for many high level carnivores in the world's oceans. Although it is known that krill do consume toxic Pseudo-nitzschi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Similarly, Ginsburg and Paul (2001) showed that A. parvula preferentially feeds on seaweeds that contain secondary metabolites at relatively low concentrations, but is deterred by high concentrations of these same compounds (Ginsburg and Paul 2001). In fact, chemical defenses of marine algae are often concentration dependent, with feeding deterrence occurring above a certain threshold value (Steinberg 1988, Bargu et al 2006). In the multiple-choice feeding assay with the female gametophyte, A. parvula preferred the more nutritious lateral branches to the main axis or the reproductive cystocarps.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ginsburg and Paul (2001) showed that A. parvula preferentially feeds on seaweeds that contain secondary metabolites at relatively low concentrations, but is deterred by high concentrations of these same compounds (Ginsburg and Paul 2001). In fact, chemical defenses of marine algae are often concentration dependent, with feeding deterrence occurring above a certain threshold value (Steinberg 1988, Bargu et al 2006). In the multiple-choice feeding assay with the female gametophyte, A. parvula preferred the more nutritious lateral branches to the main axis or the reproductive cystocarps.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of mollusks and fish contaminated with domoic acid has caused deaths and neurological damage in humans (6, 7), seabirds (10), and marine mammals (11). Dissolved domoic acid can affect marine microbial ecology by ligating micronutrients [e.g., iron (12)] and suppressing grazing by krill (13) and copepods (14). Although biological degradation in the water column has not been reported, both direct (15) and indirect (16) photodegradation contribute to domoic acid loss in seawater.…”
Section: Dom* Anmentioning
confidence: 99%
“…Effectively, when harmful algal blooms degrade, they release toxins into the dissolved phase (surrounding water). Studies have been carried out to evaluate toxin accumulation or effects of dissolved toxins on early stages of development of aquatic organisms (Colman et al, 2005;Korpinen et al, 2006;Lefebvre et al, 2005;Liu et al, 2007) on planktonic species (Babica et al, 2007;Bargu et al, 2006) and on adult fish (Bakke and Horsberg, 2010;Cazenave et al, 2005). However, very little is known about the ability of bivalve molluscs to accumulate dissolved marine biotoxins (Liu et al, 2007;Novaczek et al, 1991;Plakas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%